STUDI IN VITRO ANTIKOLESTEROL DAN FLAVONOID TOTAL DARI EKSTRAK BAWANG PUTIH TUNGGAL (Allium sativum L) - Nafiah, Azidatun; Raharjo, Danang; Ardiyantoro, Bagas (Jurnal Buana Farma, 2025)
Hypercholesterolemia is one of the main factors that increase the risk of heart and blood vessel disease, which can cause atherosclerosis and disorders in fat metabolism. Single garlic is known to contain bioactive compounds such as flavonoids that play a role in reducing cholesterol. This study aims to assess the total flavonoids and anticholesterol activity in vitro of ethanol extract of single garlic (Allium sativum L.). The extraction process was carried out using the maceration method with 96% ethanol as the solvent. Total flavonoids were measured using UV-Vis spectrophotometry with quercetin as the standard, while anticholesterol activity was tested using the Lieberman-Burchard method in vitro. The findings of this study indicate that the sample extract contains secondary metabolites such as flavonoids, alkaloids, saponins, and tannins. Single garlic shows effective flavonoid content in lowering lipid levels. The anticholesterol test shows that this extract can reduce cholesterol levels with a significant IC₅₀ value. The conclusion of this study is that single garlic has the potential as an alternative way to lower cholesterol.